The Effect Of Using U-Dictionary Application On Students’ Pronunciation Mastery At The Eleventh Grade Of SMK Negeri 1 Perbaungan - Arti Dwi Maulia, Teguh Satria Amin (Cybernetics: Journal Educational Research and Social Studies, 2023)
The objective of this research was to determine the effect of using U-Dictionary application on students’ pronunciation mastery at the eleventh grade of SMK Negeri 1 Perbaungan. This research used quantitative method with quasi-experimental design. The population of this research was class XI sudents of SMK Negeri 1 Perbaungan. The researcher selected class XI TKJ 1 with 21 students as experimental group dan class XI TKJ 3 with 21 students as control group, randomly. In collecting data, the researcher used tests to determine students’ pronunciation mastery and were carried out twice, namely pre-test and post-test. Then, the data was analyzed by using a t-test. The results showed that ttest = 8.095 and ttable with df = 40 using a two-tailed test (2-tailed) with a significance of 5% = 2.021. It shows that ttest value was higher than ttable (8.095>2.021). In oher words, Ha was accepted and H0 was rejected. On the other hand, the result of the evaluation of students’ pronunciation mastery showed that more students get predicate 4 (good) on vowel, diphthong and consonant sounds in experimental group. While in control group, more students get predicate 3 (average) and pedicate 2 (poor) on vowel, diphthong and consonant sounds. It can be concluded that using U-Dictionary application significantly affected on students’ pronunciation mastery at the eleventh grade of SMK Negeri 1 Perbaungan.